#TITLE_ALTERNATIVE# - Hanifah - Nim:15112030, Ifa
Land subsidence phenomenon in North Jakarta results in the increasing of area and depth of flood inundation. That impacts in economic losses due to structure and content damage of the buildings in the exposed area. This research aims to estimate the economic losses of the building as the result of land subsidence phenomenon in North Jakarta. The estimation process is done using RASOR (Rapid Analysis and Spatialization of Risk) Platform, because it is possible to calculate the damage faster than any manual calculation. In RASOR, HAZUS is chosen as the tool to do the calculation. The data used in the research are buildings distribution map in North Jakarta including its attributes, such as building structure and usage, and the map of Jakarta 2012 flood due to land subsidence. The result of this calculation is the estimated economic losses and damage distribution in North Jakarta. RASOR is able to estimate economic losses eventhough land subsidence phenomenon is not available as the hazard module in the platform. The result from this research shows that the total of economic losses of buildings in North Jakarta caused by land subsidence is 3.5 trillion rupiah. This losses include 2 trillion rupiah of content damage and 1.5 trillion rupiah of structure damage.